Magnetic resonance enterography (MRE) and ultrasonography (US) in the study of the small bowel in Crohn’s disease: state of the art and review of the literature - Manetta, Rosa; Capretti, Ilaria; Belleggia, Noemi; Marsecano, Claudia; Viscido, Angelo; Bruno, Federico; Arrigoni, Francesco; Ma, Liheng; Guglielmi, Giuseppe; Splendiani, Alessandra; Di Cesare, Ernesto; Masciocchi, Carlo; et al. (Acta Biomedica Atenei Parmensis, 2019)
Crohn’s disease (CD) is a chronic idiopathic disease and its diagnosis is based on a combination of clinical symptoms, laboratory tests and imaging data. There isn’t a diagnostic gold standard: the ileocolonoscopy with mucosal biopsies represents the standard for luminal disease, while cross-sectional imaging such as Ultrasound (US), Computed Tomography (CT) or Magnetic Resonance Imaging (MRI) can show transmural alterations and extraintestinal manifestations. CD is usually diagnosed in the young age and after baseline diagnosis, the patients have to undergo to variable follow-up depending on remission or active disease. The aim of our review is to compare Magnetic Resonance Enterography (MRE) to Ultrasonography (US) in the follow-up of CD.